2020
DOI: 10.1101/2020.12.20.423652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stem cell derived astrocytes withPOLGmutations and mitochondrial dysfunction including abnormal NAD+ metabolism is toxic for neurons

Abstract: The inability to reliably replicate mitochondrial DNA (mtDNA) by mitochondrial DNA polymerase gamma (POLG) leads to a subset of common mitochondrial diseases associated with neuronal death and depletion of neuronal mtDNA. Defining disease mechanisms remains difficult due to the limited access to human tissue. Astrocytes are highly abundant in the brain, playing a crucial role in the support and modulation of neuronal function. Astrocytes also respond to insults affecting the brain. Following damage to the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 49 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…A previous study in mice links mitochondrial dysfunction in astrocytes with POLG-related disease (Ignatenko et al, 2018). In an earlier study, we showed that POLG-mutant astrocytes exhibited mitochondrial dysfunction including loss of mitochondrial membrane potential, loss of ATP production, loss of complex I, disturbed NAD + /NADH metabolism, and mtDNA depletion (Liang et al, 2020a). However, whether and how POLG mutations affect mitophagy in these cells remains unclear.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…A previous study in mice links mitochondrial dysfunction in astrocytes with POLG-related disease (Ignatenko et al, 2018). In an earlier study, we showed that POLG-mutant astrocytes exhibited mitochondrial dysfunction including loss of mitochondrial membrane potential, loss of ATP production, loss of complex I, disturbed NAD + /NADH metabolism, and mtDNA depletion (Liang et al, 2020a). However, whether and how POLG mutations affect mitophagy in these cells remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…Detroit 551 fibroblasts (ATCC R CCL 110 TM ) and AG05836B fibroblasts (RRID: CVCL_2B58) were used as control lines. The generation and maintenance of iPSCs and their derived NSCs were described previously (Liang et al, 2020a(Liang et al, ,b, 2021. Astrocytes were differentiated from NSCs according to the protocol described previously (Liang et al, 2020a).…”
Section: Generation Of Induced Pluripotent Stem Cells Neural Stem Cells and Astrocyte Differentiationmentioning
confidence: 99%
See 3 more Smart Citations